Ceramic material for multilayer ceramic substrate and preparation method thereof

By using combined materials such as cerium oxide/alumina staple fiber/organic carbon composite and lithium silicate/diopside gel in ceramic materials, the problems of poor adhesion and insufficient toughness of alumina in ceramic materials are solved, and the problem of poor alumina adhesion and insufficient toughness in ceramic materials is achieved. The high-performance ceramic material preparation of ceramic substrates meets the needs of high-temperature brazing and high-density integration.

CN118978390BActive Publication Date: 2024-12-24HEBEI DINGCI ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411474199.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The adhesion of alumina and conductor materials in existing ceramic materials is poor, which cannot meet the requirements of high-temperature brazing. At the same time, the chemical inertia of alumina leads to insufficient toughness and dielectric properties in its application in ceramic substrates.

Method used

Cerium oxide/alumina staple fiber/organic carbon composites are used as toughening agents, and lithium silicate/diopside gel and hydroxyethyl cellulose modified yttrium tungstate are used as sintering aids, and carbon coating is passed The formation of glass phase improves the toughness and dielectric properties of ceramic materials, reduces the sintering temperature, and enhances the adhesion of conductors.

Benefits of technology

It significantly improves the bending strength and dielectric properties of ceramic materials, meets the requirements of high-density multi-layer radio frequency SiP and digital SiP integrated substrates, and solves the problems of conductor adhesion and sintering temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of ceramic technology, and more specifically, to a ceramic material for a multilayer ceramic substrate and a preparation method thereof. The ceramic material for the multilayer ceramic substrate comprises raw materials including alumina, cerium oxide / alumina short fiber / organic carbon composite and a sintering aid; the sintering aid comprises lithium silicate / diopside gel and yttrium tungstate modified by hydroxyethyl cellulose. The present invention solves the problem that the alumina in the ceramic material has poor adhesion to the conductor material and cannot meet the requirements of high-temperature brazing. At the same time, the ceramic material provided by the present invention has a lower dielectric constant and dielectric loss tangent, and has a higher bending strength, meeting the requirements of a high-density multilayer RF SiP integrated substrate and a digital SiP integrated substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic technology, and more specifically, to a ceramic material for a multilayer ceramic substrate and a preparation method thereof. Background Art

[0002] With the rapid development of large-scale integrated circuits, consumers have more stringent requirements for the miniaturization, integration and reliability of electronic devices. The heat dissipation performance of electronic components plays an important role in the normal operation of the equipment. Ceramic substrates are increasingly widely used in electronic components due to their excellent electrical insulation, high thermal conductivity, low thermal expansion coefficient and good chemical stability.

[0003] In order to further improve the packaging integration and miniaturization of electronic components, the high-temperature multilayer co-fired ceramic, or HTCC (High Temperature co-fired Ceramic) technology, has been developed. The high-temperature conductor paste is combined with the cast sheet by printing and filling methods according to the circuit design requirements. After multiple layers of lamination, it is finally co-fired into an integrated shape.

[0004] Ceramic powders mainly include alumina, aluminum nitride and boron nitride. Aluminum nitride has excellent performance but is expensive. Boron nitride is difficult to process due to its high hardness. Alumina has a high cost-effectiveness and has excellent application prospects in HTCC products.

[0005] The Chinese patent with publication number CN109437863A discloses a high-strength HTCC ceramic material and its preparation method. The high-strength HTCC ceramic material is composed of 60% to 90% micron-grade aluminum oxide, 0.1% to 30% submicron-grade aluminum oxide, 3% to 5% kaolin, 3% to 5% talc, 1% to 3% chromium trioxide, 1% to 3% molybdenum trioxide, and 0.1% to 1% yttrium oxide according to weight percentage. The technical solution reduces the porosity of the ceramic material and improves the density and bending strength of the ceramic material by introducing submicron-grade aluminum oxide. A Chinese patent with publication number CN116332627A discloses a low thermal expansion coefficient high-temperature co-fired ceramic material, comprising the following raw materials in parts by weight: 70% to 90% micron-grade alumina, 1% to 20% submicron-grade alumina, 3% to 5% cordierite, 3% to 5% β-eucryptite, 1% to 3% chromium trioxide, 1% to 3% molybdenum trioxide, 0.1% to 1% yttrium oxide, and a number of casting aids. This technical solution reduces the porosity of the ceramic material by introducing cordierite and β-eucryptite, and at the same time introduces submicron-grade alumina, which can reduce the thermal expansion coefficient of the ceramic material while improving the density, thermal conductivity and flexural strength of the ceramic material, thereby achieving the effect of improving the thermal shock resistance of the ceramic material.

[0006] However, both of the above two technical solutions fail to solve the problem that alumina is not easy to form good adhesion with conductive materials due to its high chemical inertness, which makes it difficult for conductive materials (such as metals) to form a strong bond on the ceramic surface during brazing. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention aims to provide a ceramic material for a multilayer ceramic substrate and a preparation method thereof, so as to solve the problem that the adhesion between the aluminum oxide in the ceramic material and the conductor material is poor and cannot meet the requirements of high-temperature brazing. At the same time, the ceramic material provided by the present invention has a lower dielectric constant and dielectric loss tangent, and has a higher bending strength, which meets the requirements of a high-density multilayer RF SiP integrated substrate and a digital SiP integrated substrate.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The first aspect of the present invention provides a ceramic material for a multilayer ceramic substrate, wherein the raw materials include alumina, a toughening agent and a sintering aid, wherein the mass ratio of the alumina, the toughening agent and the sintering aid is (92-97): (1-3): (2-5); the toughening agent is a cerium oxide / alumina short fiber / organic carbon composite; the sintering aid includes lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate; the mass ratio of the lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate is (1-3): (2-4).

[0010] Alumina ceramics have poor toughness, and in order to solve this problem, a toughening agent needs to be introduced. Alumina short fibers have a large aspect ratio, which can theoretically improve the toughness of ceramic materials. However, alumina short fibers form a strong bonding interface with the ceramic matrix in the toughening matrix, which is not conducive to the debonding and pull-out of the fibers. In addition, alumina fibers will also undergo partial crystal phase transformation and secondary crystallization at a certain temperature during high temperature processes, thereby affecting the toughening effect of the fibers. In order to solve this problem, the inventors found that when cerium oxide / aluminum oxide short fiber / organic carbon composite is used as a toughening agent, the cerium oxide in the cerium oxide / aluminum oxide short fiber / organic carbon composite is dispersed in the alumina short fiber, and a carbon coating layer is formed on the surface of the alumina short fiber dispersed with cerium oxide, which can avoid sintering of the fibers or ceramic groups into one during the sintering process. Therefore, the alumina short fibers can be interlocked, so that the fibers have a bridging effect when the local cracks are small, and bear greater external stress. At the same time, under the action of sintering pressure, granular cerium oxide is more likely to precipitate and fill in the alumina grain boundaries, serving as a resistance point for the cracks, hindering the expansion of the cracks, thereby increasing the toughness of the ceramic material. At the same time, the inventors unexpectedly found that the cerium oxide / aluminum oxide short fiber / organic carbon composite also improves the dielectric properties of the ceramic material.

[0011] In addition to reducing the sintering temperature of ceramic materials, sintering aids can also melt at high temperatures to form a glass phase that migrates toward the metal, promoting the bonding of ceramic materials and conductors. The most common method for sintering aids is to use ball milling and mixing with the main phase ceramic powder. However, this method requires strict control of the particle size of the sintering aid, long ball milling time, and unsatisfactory mixing effect. During the experiment, the inventors found that when the sintering aid includes lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate, the sintering temperature can be effectively reduced. It was unexpectedly discovered that this technical solution solves the problem that the conductor adhesion of ceramic materials cannot meet the requirements of high-temperature brazing when used in multi-layer ceramic substrates. The inventors speculate that this is because lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate respectively coat the cerium oxide / aluminum oxide short fiber / organic carbon composite through the gel effect and the polar group effect of hydroxyethyl cellulose, and the two act synergistically to change the interface effect of the ceramic material, reduce the difference in thermal expansion coefficient between the ceramic material and the metal conductor, and the glass phase is more likely to flow into the metallization layer during high-temperature brazing, and mechanically interlock the metal and ceramic particles, thereby generating strong interface adhesion, and forming a dense composite metallization layer by filling the pores.

[0012] Preferably, the mass ratio of the lithium silicate / diopside gel to the hydroxyethyl cellulose-modified yttrium tungstate is 2:3.

[0013] Preferably, the alumina comprises α-phase alumina A with a particle size of 0.3-0.8 μm, α-phase alumina B with a particle size of 30-80 nm, and γ-phase alumina C with a particle size of 30-80 nm.

[0014] Preferably, the mass ratio of the α-phase aluminum oxide A, α-phase aluminum oxide B and γ-phase aluminum oxide C is (10-30): (65-85): (0.5-1), preferably 25:70:0.8.

[0015] Preferably, the cerium oxide / aluminium oxide short fiber / organic carbon composite comprises a cerium oxide / aluminium oxide short fiber / organic carbon composite A and a cerium oxide / aluminium oxide short fiber / organic carbon composite B;

[0016] The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon composite A comprises the following steps:

[0017] S1. Add 0.2-0.5 parts by mass of cerium oxide, 3-5 parts by mass of aluminum oxide short fibers and 0.4-0.6 parts by mass of 30-40 wt% of organic carbon to 8-10 parts by mass of ethanol, add 0.5-1 parts by mass of a surfactant, and perform ball milling to obtain slurry A. Sand mill slurry A to obtain slurry B. Spray dry slurry B to obtain powder A.

[0018] S2, pre-sintering powder A; mixing the pre-sintered product with the remaining organic carbon, adding 8-10 parts by mass of ethanol, and ball milling to obtain slurry C, spray drying the slurry C to obtain powder B, and performing secondary sintering on powder B to obtain the cerium oxide / aluminum oxide short fiber / organic carbon composite A;

[0019] The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon source composite B is different from that of the cerium oxide / aluminum oxide short fiber / organic carbon source composite A only in that the powder A is directly sintered to obtain the cerium oxide / aluminum oxide short fiber / organic carbon source composite B.

[0020] Preferably, the mass ratio of the cerium oxide / aluminum oxide short fibers / organic carbon composite A to the cerium oxide / aluminum oxide short fibers / organic carbon composite B is (5-7):(2-4), preferably 6:3.

[0021] The inventor unexpectedly discovered during the experiment that when the cerium oxide / aluminum oxide short fiber / organic carbon composite in the present invention includes cerium oxide / aluminum oxide short fiber / organic carbon composite A and cerium oxide / aluminum oxide short fiber / organic carbon composite B, the flexural strength of the ceramic material is significantly improved. The inventor speculates that this is because the cerium oxide / aluminum oxide short fiber / organic carbon composite A is sintered twice to form a double-layer carbon coating on the surface of the cerium oxide / aluminum oxide short fiber, while the cerium oxide / aluminum oxide short fiber / organic carbon composite B is only sintered once to form a single-layer carbon coating on the surface of the cerium oxide / aluminum oxide short fiber. The particle sizes and structures of the two are different. When the two are mixed and used, they can complement each other, effectively deflect cracks and release crack tip stress through bridging, debonding or pulling out, and at the same time, it is more conducive to the formation of a dense structure of the ceramic material and the refinement of the grains, so the flexural performance of the ceramic material is improved.

[0022] Preferably, the rotation speed of the ball mill in step S1 and step S2 is 500-800 rpm, and the ball milling time is 1-3 h.

[0023] Preferably, the rotation speed of the sand milling in step S1 and step S2 is 3000-5000 rpm, and the sand milling time is 2-4 hours.

[0024] Preferably, the outlet temperature of the spray drying in step S1 and step S2 is 100-120°C.

[0025] Preferably, the pre-sintering temperature in step S2 is 300-400° C., and the pre-sintering time is 3-4 hours.

[0026] Preferably, the temperature of the secondary sintering in step S2 is 600-700° C., and the time of the secondary sintering is 6-8 hours.

[0027] Preferably, the organic carbon is glucose or sucrose.

[0028] Preferably, the surfactant is selected from at least one of octylphenol polyoxyethylene ether, castor oil polyoxyethylene ether and fatty alcohol polyoxyethylene ether.

[0029] Preferably, the particle size of the cerium oxide is 20-50 nm.

[0030] Preferably, the alumina short fibers are composed of 85-88% α-alumina and 12-15% silica.

[0031] Preferably, the average diameter of the alumina short fibers is 4-7 μm.

[0032] Preferably, the preparation method of the lithium silicate / diopside gel comprises the following steps: dissolving lithium hydroxide in water to obtain a lithium hydroxide solution; adding acidic silica sol to the lithium hydroxide solution, stirring at 20-25°C for 20-30 minutes, heating to 50-60°C and aging for 1-2 hours to obtain lithium silicate sol; adding diopside powder to the lithium silicate sol, mixing evenly, and adding a complexing agent to obtain the lithium silicate / diopside gel.

[0033] Preferably, the concentration of the lithium hydroxide solution is 0.5-1 mol / L.

[0034] Preferably, the mass ratio of the acidic silica sol to lithium hydroxide is (2-4):1.

[0035] Preferably, the mass ratio of the lithium silicate sol, diopside powder and complexing agent is (1-3): (0.5-1.5): (0.5-1.5).

[0036] Preferably, the complexing agent is citric acid.

[0037] Preferably, the preparation method of the hydroxyethyl cellulose modified yttrium tungstate comprises the following steps: ball-milling yttrium tungstate doped with tin and indium and hydroxyethyl cellulose in water and drying them to obtain the hydroxyethyl cellulose modified yttrium tungstate.

[0038] Preferably, the mass ratio of the tin- and indium-doped yttrium tungstate, hydroxyethyl cellulose and water is 1:(1.5-2):(10-20).

[0039] Preferably, the ball milling speed is 500-800 rpm, and the ball milling time is 6-10 h.

[0040] Preferably, the preparation method of the tin- and indium-doped yttrium tungstate comprises the following steps: dissolving ammonium tungstate in water, adding hydrogen peroxide, and stirring to obtain solution A; adding yttrium carbonate, tin nitrate and indium nitrate to solution A, heating and stirring to obtain a gel; and drying and calcining the gel to obtain the tin- and indium-doped yttrium tungstate.

[0041] The inventors found in the experimental process that when pure yttrium tungstate is modified by hydroxyethyl cellulose, the sintering effect is not good, and the dielectric properties of the ceramic material are reduced. However, when yttrium tungstate doped with tin and indium is modified by hydroxyethyl cellulose, not only the dielectric properties of the ceramic material can be improved, but also the bending strength of the ceramic material is improved. The inventors speculate that this is because, on the one hand, tin and indium have low melting points, which can reduce the melting point of the solid solution of the ceramic material system, reduce the viscosity of the high-temperature liquid phase, produce enough liquid phase, improve the compactness of the ceramic material, and improve the bending strength. On the other hand, it can reduce the mismatch between the thermal expansion coefficient of the generated phase and the ceramic material, avoid the ceramic material from easily generating microcracks during the cooling process, and then improve the dielectric properties of the ceramic material.

[0042] The present invention further discovered during the experiment that the comprehensive performance of the ceramic material is optimal only when the mass ratio of alumina, toughening agent and sintering aid is (92-97): (1-3): (2-5). When one component exceeds this mass ratio, the dielectric constant, dielectric loss, toughness, bending resistance and adhesion of the ceramic material will all decrease.

[0043] Preferably, the mass ratio of ammonium tungstate, water and hydrogen peroxide is (5-7):(15-18):1.

[0044] Preferably, the mass ratio of yttrium carbonate, tin nitrate and indium nitrate is (30-40):(1-2):(1-2).

[0045] Preferably, the heating and stirring is carried out at a temperature of 50-60°C and for a time of 4-6 hours.

[0046] Preferably, the drying temperature is 80-100° C. and the drying time is 1-2 h.

[0047] Preferably, the calcination temperature is 900-1000° C. and the calcination time is 5-7 h.

[0048] The second aspect of the present invention provides a method for preparing a ceramic material for a multilayer ceramic substrate, comprising the following steps: uniformly mixing alumina, a toughening agent and a sintering aid, and sintering at 1000-1200° C. for 1-3 hours to obtain the ceramic material.

[0049] Beneficial Effects

[0050] 1. When the cerium oxide / aluminum oxide short fiber / organic carbon composite is used as a toughening agent in the present invention, the cerium oxide in the cerium oxide / aluminum oxide short fiber / organic carbon composite is dispersed in the alumina short fiber, and a carbon coating layer is formed on the surface of the alumina short fiber dispersed with cerium oxide, which can prevent the fibers or ceramic groups from sintering together during the sintering process. Therefore, the alumina short fibers can be interlocked, so that the fibers have a bridging effect when the local cracks are small, and bear greater external stress. At the same time, under the action of the sintering pressure, the granular cerium oxide is more likely to precipitate and fill in the alumina grain boundaries, serving as a resistance point for the cracks, hindering the expansion of the cracks, thereby increasing the toughness of the ceramic material. At the same time, the inventors unexpectedly discovered that the cerium oxide / aluminum oxide short fiber / organic carbon composite also improves the dielectric properties of the ceramic material.

[0051] 2. When the sintering aids of the present invention include lithium silicate / diopside gel and yttrium tungstate modified with hydroxyethyl cellulose, the sintering temperature can be effectively reduced. It is unexpectedly found that this technical solution solves the problem that the conductor adhesion of ceramic materials cannot meet the high-temperature brazing requirements when used for multi-layer ceramic substrates.

[0052] 3. In the present invention, when the cerium oxide / aluminum oxide short fiber / organic carbon composite includes cerium oxide / aluminum oxide short fiber / organic carbon composite A and cerium oxide / aluminum oxide short fiber / organic carbon composite B, the flexural strength of the ceramic material is significantly improved.

[0053] 4. When yttrium tungstate doped with tin and indium is modified by hydroxyethyl cellulose, the dielectric properties of the ceramic material can be improved, and the bending strength of the ceramic material can also be improved.

[0054] 5. When the mass ratio of alumina, toughening agent and sintering aid is controlled to (92-97): (1-3): (2-5), the dielectric constant, dielectric loss, toughness, bending resistance and adhesion of the ceramic material are avoided to decrease. DETAILED DESCRIPTION

[0055] In order to better explain the present invention, the following will combine the examples in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. The embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0056] In the following examples, unless otherwise specified, the operating methods used are all conventional operating methods, the equipment used are all conventional equipment, and the raw materials used are all commercially available.

[0057] The raw materials used in the examples and comparative examples of the present invention are:

[0058] α-alumina A, α-alumina B, and γ-alumina C were all purchased from Zhengzhou Lvsong New Material Technology Co., Ltd.;

[0059] Octylphenol polyoxyethylene ether, purchased from Hai'an Petrochemical Plant, Jiangsu Province, model: OP-4;

[0060] Cerium oxide, purchased from Brofos Nanotechnology (Ningbo) Co., Ltd., model: Brofos-CeO2-35;

[0061] Alumina short fibers, purchased from Shandong Dongheng Guoxian New Materials Co., Ltd., model: 85;

[0062] Acidic silica sol, purchased from Zhejiang Yuda Chemical Co., Ltd., model: HS-2-20;

[0063] Hydroxyethyl cellulose was purchased from Feicheng Yutian Chemical Co., Ltd.

[0064] Example 1

[0065] The ceramic material for a multilayer ceramic substrate comprises raw materials including alumina, cerium oxide / aluminum oxide short fiber / organic carbon composite and a sintering aid; the sintering aid comprises lithium silicate / diopside gel and yttrium tungstate modified by hydroxyethyl cellulose.

[0066] The mass ratio of the alumina, toughening agent and sintering aid is 94:2:4.

[0067] The mass ratio of the lithium silicate / diopside gel to the hydroxyethyl cellulose-modified yttrium tungstate is 2:3.

[0068] The alumina includes α-phase alumina A with a particle size of 0.4±0.1 μm, α-phase alumina B with a particle size of 50 nm, and γ-phase alumina C with a particle size of 50 nm.

[0069] The mass ratio of the α-phase aluminum oxide A, the α-phase aluminum oxide B and the γ-phase aluminum oxide C is 25:70:0.8.

[0070] The cerium oxide / aluminum oxide short fiber / organic carbon composite comprises cerium oxide / aluminum oxide short fiber / organic carbon composite A and cerium oxide / aluminum oxide short fiber / organic carbon composite B; the mass ratio of the cerium oxide / aluminum oxide short fiber / organic carbon composite A and the cerium oxide / aluminum oxide short fiber / organic carbon composite B is 6:3.

[0071] The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon composite A comprises the following steps:

[0072] S1. Add 0.4 parts by mass of cerium oxide, 4 parts by mass of aluminum oxide short fibers and 0.5 parts by mass of 30 wt% organic carbon to 10 parts by mass of ethanol, add 0.8 parts by mass of a surfactant, and ball-mill to obtain slurry A. Sand-mill slurry A to obtain slurry B. Spray-dry slurry B to obtain powder A.

[0073] S2, pre-sintering powder A; mixing the pre-sintered product with the remaining organic carbon, adding 10 parts by mass of ethanol, and ball milling to obtain slurry C, spray drying the slurry C to obtain powder B, and performing secondary sintering on powder B to obtain the cerium oxide / aluminum oxide short fiber / organic carbon composite A;

[0074] The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon source composite B is different from that of the cerium oxide / aluminum oxide short fiber / organic carbon source composite A only in that the powder A is directly sintered to obtain the cerium oxide / aluminum oxide short fiber / organic carbon source composite B.

[0075] The rotation speed of the ball mill in step S1 and step S2 is 600 rpm, and the ball milling time is 2 h.

[0076] The rotation speed of the sanding in step S1 and step S2 is 4000 rpm, and the sanding time is 3 hours.

[0077] The outlet temperature of the spray drying in step S1 and step S2 is 110°C.

[0078] The pre-sintering temperature in step S2 is 350° C., and the pre-sintering time is 3.5 h.

[0079] The temperature of the secondary sintering in step S2 is 650° C., and the time of the secondary sintering is 7 hours.

[0080] The organic carbon is glucose.

[0081] The surfactant is octylphenol polyoxyethylene ether.

[0082] The particle size of the cerium oxide is 35 nm.

[0083] The alumina short fibers are composed of 85-88% α-alumina and 12-15% silica.

[0084] The average diameter of the alumina short fibers is 4-7 μm.

[0085] The preparation method of the lithium silicate / diopside gel comprises the following steps: lithium hydroxide is dissolved in water to obtain a lithium hydroxide solution; acidic silica sol is added to the lithium hydroxide solution, stirred at 25° C. for 25 minutes, heated to 60° C. and aged for 1.5 hours to obtain lithium silicate sol; diopside powder is added to the lithium silicate sol, mixed evenly, and then a complexing agent is added to obtain the lithium silicate / diopside gel.

[0086] The concentration of the lithium hydroxide solution is 1 mol / L.

[0087] The mass ratio of the acidic silica sol to lithium hydroxide is 3:1.

[0088] The mass ratio of the lithium silicate sol, diopside powder and complexing agent is 3:1:1.

[0089] The complexing agent is citric acid.

[0090] The preparation method of hydroxyethyl cellulose modified yttrium tungstate comprises the following steps: Yttrium tungstate doped with tin and indium and hydroxyethyl cellulose are ball-milled and dried in water to obtain the hydroxyethyl cellulose modified yttrium tungstate.

[0091] The mass ratio of the tin- and indium-doped yttrium tungstate, hydroxyethyl cellulose and water is 1:2:18.

[0092] The ball milling speed is 600 rpm, and the ball milling time is 8 h.

[0093] The preparation method of yttrium tungstate doped with tin and indium comprises the following steps: dissolving ammonium tungstate in water, adding hydrogen peroxide, and stirring to obtain solution A; adding yttrium carbonate, tin nitrate and indium nitrate to solution A, heating and stirring to obtain gel; and drying and calcining the gel to obtain the yttrium tungstate doped with tin and indium.

[0094] The mass ratio of the ammonium tungstate, water and hydrogen peroxide is 6:18:1.

[0095] The mass ratio of the yttrium carbonate, tin nitrate and indium nitrate is 35:1:2.

[0096] The heating and stirring was performed at 60°C for 5 hours.

[0097] The drying temperature is 90° C. and the drying time is 1.5 h.

[0098] The calcination temperature is 900° C. and the calcination time is 6 hours.

[0099] The method for preparing a ceramic material for a multilayer ceramic substrate comprises the following steps: uniformly mixing alumina, a toughening agent and a sintering aid, and sintering the mixture at 1100° C. for 2 hours to obtain the ceramic material.

[0100] Example 2

[0101] The difference from Example 1 is that the mass ratio of the alumina, toughening agent and sintering aid is 92:3:5, the mass ratio of the lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate is 1:2, and the rest are the same.

[0102] Example 3

[0103] The difference from Example 1 is that the mass ratio of the alumina, toughening agent and sintering aid is 97:1:2, the mass ratio of the lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate is 3:4, and the rest are the same.

[0104] Comparative Example 1

[0105] The difference from Example 1 is that the mass ratio of the alumina, toughening agent and sintering aid is 90:4:6, and the rest are the same.

[0106] Comparative Example 2

[0107] The difference from Example 1 is that cerium oxide / aluminum oxide short fiber / organic carbon composite A is replaced by alumina short fiber / organic carbon composite A, and cerium oxide / aluminum oxide short fiber / organic carbon composite B is replaced by alumina short fiber / organic carbon composite B, and the rest are the same.

[0108] The preparation method of alumina short fiber / organic carbon composite A comprises the following steps:

[0109] S1. Add 4 parts by mass of alumina short fibers and 0.5 parts by mass of 30 wt% organic carbon to 10 parts by mass of ethanol, add 0.8 parts by mass of a surfactant, and ball-mill to obtain slurry A. Sand-mill slurry A to obtain slurry B. Spray-dry slurry B to obtain powder A.

[0110] S2, pre-sintering powder A; mixing the pre-sintered product with the remaining organic carbon, adding 10 parts by mass of ethanol, and ball milling to obtain slurry C, spray drying the slurry C to obtain powder B, and performing secondary sintering on powder B to obtain the cerium oxide / aluminum oxide short fiber / organic carbon composite A;

[0111] The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon source composite B is different from that of the cerium oxide / aluminum oxide short fiber / organic carbon source composite A only in that the powder A is directly sintered to obtain the cerium oxide / aluminum oxide short fiber / organic carbon source composite B.

[0112] Comparative Example 3

[0113] The difference from Example 1 is that cerium oxide / aluminum oxide short fibers / organic carbon composite A is replaced with alumina short fibers / organic carbon composite B of the same mass, and the rest are the same.

[0114] Comparative Example 4

[0115] The difference from Example 1 is that cerium oxide / aluminum oxide short fibers / organic carbon composite B is replaced with alumina short fibers / organic carbon composite A of the same mass, and the rest are the same.

[0116] Comparative Example 5

[0117] The difference from Example 1 is that the yttrium tungstate modified with hydroxyethyl cellulose is replaced with lithium silicate / diopside gel of the same mass, and the rest are the same.

[0118] Comparative Example 6

[0119] The difference from Example 1 is that the lithium silicate / diopside gel is replaced by yttrium tungstate modified with hydroxyethyl cellulose of the same mass, and the rest are the same.

[0120] Comparative Example 7

[0121] The difference from Example 1 is that the yttrium tungstate doped with tin and indium modified by hydroxyethyl cellulose is replaced by yttrium tungstate modified by hydroxyethyl cellulose of the same mass, and the rest is the same.

[0122] Performance Test:

[0123] The ceramic materials of Examples 1-3 and Comparative Examples 1-7 were tested as follows:

[0124] 1. Bending strength: tested according to GB / T 6569-2006 standard, the results are shown in Table 1;

[0125] 2. Fracture toughness: tested according to GB / T23806-2009 standard, the results are shown in Table 1;

[0126] 3. Dielectric constant and dielectric loss tangent: tested according to GB / T 5594.4-2015 standard, the results are shown in Table 1;

[0127] 4. Conductor adhesion: Alumina-based HTCC ceramics were prepared by conventional tape casting in the art, wherein metal (tungsten) ink was printed on a diaphragm (diaphragm thickness was 100 μm) using screen printing technology, with 3 layers stacked, sintered at 1550°C for 3 h in a wet nitrogen and hydrogen atmosphere, nickel plated with 2 μm and gold plated with 2 μm, and then a copper wire with a diameter of 0.5 mm was welded to the ceramic at 800°C. The shear strength was tested by loading at a rate of 1 mm / min using a standard universal testing machine. The results are shown in Table 1.

[0128] Table 1 Performance test results of ceramic materials of Examples 1-3 and Comparative Examples 1-7

[0129]

[0130] It can be seen from Table 1 that:

[0131] The flexural strength of the ceramic materials of Example 1 and Example 2 is ≥472MPa, and the fracture toughness is ≥9.6MPa·m 1 / 2 , dielectric constant ≤6.3, dielectric loss tangent ≤0.002, conductor adhesion ≥50MPa;

[0132] The flexural strength of the ceramic material of Example 3 is 465 MPa and the fracture toughness is 9.1 MPa·m 1 / 2 , the dielectric constant is 6.5, the dielectric loss tangent is 0.007, and the conductor adhesion is 48MPa;

[0133] Comparative Example 1: Since the mass ratio of alumina, toughening agent and sintering aid is not in the range of (92-97): (1-3): (2-5), the flexural strength, fracture toughness, dielectric constant, dielectric loss tangent and conductor adhesion of the ceramic material are all reduced;

[0134] Comparative Example 2: Cerium oxide / aluminum oxide short fiber / organic carbon composite A is replaced by alumina short fiber / organic carbon composite A, and cerium oxide / aluminum oxide short fiber / organic carbon composite B is replaced by alumina short fiber / organic carbon composite B. The fracture toughness of the ceramic material decreases to 6.8 MPa·m 1 / 2 , dielectric constant and dielectric loss tangent are 7.3 and 0.0034 respectively; other properties also decrease to varying degrees;

[0135] In comparative example 3, cerium oxide / aluminum oxide short fiber / organic carbon composite A was replaced with an equal mass of alumina short fiber / organic carbon composite B, and in comparative example 4, cerium oxide / aluminum oxide short fiber / organic carbon composite B was replaced with an equal mass of alumina short fiber / organic carbon composite A. The flexural strength of the ceramic material decreased to 448 MPa and 436 MPa, respectively, and other properties also decreased to varying degrees.

[0136] In comparative example 5, yttrium tungstate modified by hydroxyethyl cellulose was replaced by lithium silicate / diopside gel of the same mass, and in comparative example 6, lithium silicate / diopside gel was replaced by yttrium tungstate modified by hydroxyethyl cellulose of the same mass. The conductor adhesion of the ceramic material decreased to 31 and 35 MPa, respectively, and other properties also decreased to varying degrees.

[0137] In Comparative Example 7, the yttrium tungstate doped with tin and indium modified by hydroxyethyl cellulose was replaced with yttrium tungstate modified by hydroxyethyl cellulose of equal mass. The flexural strength of the ceramic material decreased to 442 MPa, and the dielectric constant and dielectric loss tangent were 8.8 and 0.043 respectively. Other properties also decreased to varying degrees.

[0138] The above description is only a specific embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent transformation made by using the present invention, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

Claims

1. A ceramic material for a multilayer ceramic substrate, characterized in that: The raw materials include alumina, a toughening agent and a sintering aid, wherein the mass ratio of the alumina, the toughening agent and the sintering aid is (92-97): (1-3): (2-5); the toughening agent is a cerium oxide / alumina short fiber / organic carbon composite; the sintering aid includes lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate; the mass ratio of the lithium silicate / diopside gel and hydroxyethyl cellulose modified yttrium tungstate is (1-3): (2-4); The cerium oxide / aluminium oxide short fiber / organic carbon composite comprises a cerium oxide / aluminium oxide short fiber / organic carbon composite A and a cerium oxide / aluminium oxide short fiber / organic carbon composite B; The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon composite A comprises the following steps: S1. Add 0.2-0.5 parts by mass of cerium oxide, 3-5 parts by mass of aluminum oxide short fibers and 0.4-0.6 parts by mass of 30-40 wt% of organic carbon to 8-10 parts by mass of ethanol, add 0.5-1 parts by mass of a surfactant, and perform ball milling to obtain slurry A. Sand mill slurry A to obtain slurry B. Spray dry slurry B to obtain powder A. S2, pre-sintering powder A; mixing the pre-sintered product with the remaining organic carbon, adding 8-10 parts by mass of ethanol, and ball milling to obtain slurry C, spray drying the slurry C to obtain powder B, and performing secondary sintering on powder B to obtain the cerium oxide / aluminum oxide short fiber / organic carbon composite A; The preparation method of the cerium oxide / aluminum oxide short fiber / organic carbon composite B is different from that of the cerium oxide / aluminum oxide short fiber / organic carbon source composite A in that the powder A is directly sintered to obtain the cerium oxide / aluminum oxide short fiber / organic carbon composite B; The preparation method of the lithium silicate / diopside gel comprises the following steps: dissolving lithium hydroxide in water to obtain a lithium hydroxide solution; adding acidic silica sol to the lithium hydroxide solution, stirring at 20-25° C. for 20-30 minutes, heating to 50-60° C. and aging for 1-2 hours to obtain lithium silicate sol; adding diopside powder to the lithium silicate sol, mixing evenly, and then adding a complexing agent to obtain the lithium silicate / diopside gel; The preparation method of hydroxyethyl cellulose modified yttrium tungstate comprises the following steps: Yttrium tungstate doped with tin and indium and hydroxyethyl cellulose are ball-milled and dried in water to obtain the hydroxyethyl cellulose modified yttrium tungstate.

2. The ceramic material for a multilayer ceramic substrate according to claim 1, characterized in that: The alumina comprises α-phase alumina A with a particle size of 0.3-0.8 μm, α-phase alumina B with a particle size of 30-80 nm and γ-phase alumina C with a particle size of 30-80 nm; the mass ratio of the α-phase alumina A, α-phase alumina B and γ-phase alumina C is (10-30): (65-85): (0.5-1).

3. The ceramic material for a multilayer ceramic substrate according to claim 1, characterized in that: The mass ratio of the lithium silicate sol to the diopside powder is (1-3): (0.5-1.5).

4. The ceramic material for a multilayer ceramic substrate according to claim 1, characterized in that: The mass ratio of the yttrium tungstate doped with tin and indium, hydroxyethyl cellulose and water is 1:(1.5-2):(10-20).

5. The ceramic material for a multilayer ceramic substrate according to claim 4, characterized in that: The preparation method of yttrium tungstate doped with tin and indium comprises the following steps: dissolving ammonium tungstate in water, adding hydrogen peroxide, and stirring to obtain solution A; adding yttrium carbonate, tin nitrate and indium nitrate to solution A, heating and stirring to obtain gel; and drying and calcining the gel to obtain the yttrium tungstate doped with tin and indium.

6. The ceramic material for a multilayer ceramic substrate according to claim 5, characterized in that: The mass ratio of yttrium carbonate, tin nitrate and indium nitrate is (30-40): (1-2): (1-2).

7. The method for preparing a ceramic material for a multilayer ceramic substrate according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing alumina, a toughening agent and a sintering aid uniformly and sintering the mixture at 1000-1200° C. for 1-3 hours to obtain the ceramic material.